2022
DOI: 10.3390/s22031077
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Sensor Algorithm to Estimate Walk Distance

Abstract: The “total distance walked” obtained during a standardized walking test is an integral component of physical fitness and health status tracking in a range of consumer and clinical applications. Wearable inertial sensors offer the advantages of providing accurate, objective, and reliable measures of gait while streamlining walk test administration. The aim of this study was to develop an inertial sensor-based algorithm to estimate the total distance walked using older subjects with impaired fasting glucose (Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Between-study differences in procedures, populations and reference methods make comparisons between studies problematic. However, the study by Shah et al [23] evaluated a similar type of technology to that assessed in the current study, used analogous age-based inclusion criteria, and had a comparable sample size. The results of Shah et al demonstrated that the commercially available IMU being tested had a MAE of 19.77 m for 6MWTs conducted on a 15-m track and an MAE of 18.36 m when the tests were conducted on a 20-m track.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between-study differences in procedures, populations and reference methods make comparisons between studies problematic. However, the study by Shah et al [23] evaluated a similar type of technology to that assessed in the current study, used analogous age-based inclusion criteria, and had a comparable sample size. The results of Shah et al demonstrated that the commercially available IMU being tested had a MAE of 19.77 m for 6MWTs conducted on a 15-m track and an MAE of 18.36 m when the tests were conducted on a 20-m track.…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance and widespread use of the 6MWT in clinical practice, there has been great interest in proposing wearable devices or smartphone applications as potential solutions for enhancing this assessment. Indeed, the precision of several potential solutions for enhancing the 6MWD has been assessed in previous studies, including evaluations of a commercially available wearable inertial measurement unit (IMU) [23], the iPhone's built-in algorithm [24], purpose-built smartphone-based algorithms [25][26][27] and a custom machine-learning algorithm [28]. While some of these studies yielded good results, use of several of these applications had the disadvantage of requiring a priori information such as the patient's height [25] or the course length [26,27], or pre-calibration for each subject being tested [28].…”
Section: Introductionmentioning
confidence: 99%
“…Also within the context of the 6MWT, studies propose using smartphones IMUs [ 9 , 16 ]. For example, Mak et al [ 8 ] conducted an extensive study concerning in-clinic and home-based 6MWT using inertial sensors embedded in iPhone 7 smartphones, Apple.Their findings are promising, but rely only on the step count, as measuring distance from IMU is not easy to achieve reliably.…”
Section: Related Workmentioning
confidence: 99%
“…Measuring the total distance walked is crucial in tracking physical fitness and health status, but current methods can be subjective and time-consuming. Shah et al [8] developed an algorithm, based on inertial sensors, to estimate the total distance walked by older adults and patients with multiple sclerosis. The algorithm calculates the distance travelled during each step and the total distance walked as the sum of walk distances for each stride, including turns.…”
Section: Contributionsmentioning
confidence: 99%